2018
DOI: 10.1509/jmr.15.0346
|View full text |Cite
|
Sign up to set email alerts
|

The Teasing Effect: An Underappreciated Benefit of Creating and Resolving an Uncertainty

Abstract: Seven studies covering diverse contexts show an underappreciated benefit of teasing in information acquisition: first creating and then resolving an uncertainty can generate a net positive experience, yet laypeople do not seek out this process. For example, trivia readers report better hedonic experiences if they are first teased with some missing information and then given that information than if they receive all the information at the same time; however, when given a choice, readers prefer to receive all in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 93 publications
(164 reference statements)
2
68
0
9
Order By: Relevance
“…One of the reasons why this idea has attracted popularity is that it can explain strong seductive power of curiosity, which sometimes lead people to make irrational decisions (e.g., Hsee and Ruan 2016;Lau et al 2018;Oosterwijk 2017). However, this idea is still controversial and empirical evidence is not conclusive (Ruan et al 2018;Silvia 2006). For example, Jepma et al (2012) found that presentation of ambiguous pictures (i.e., material that is likely to trigger perceptual curiosity) activates the anterior cingulate cortex and anterior insular cortex.…”
Section: Curiosity As An Aversive Statementioning
confidence: 99%
“…One of the reasons why this idea has attracted popularity is that it can explain strong seductive power of curiosity, which sometimes lead people to make irrational decisions (e.g., Hsee and Ruan 2016;Lau et al 2018;Oosterwijk 2017). However, this idea is still controversial and empirical evidence is not conclusive (Ruan et al 2018;Silvia 2006). For example, Jepma et al (2012) found that presentation of ambiguous pictures (i.e., material that is likely to trigger perceptual curiosity) activates the anterior cingulate cortex and anterior insular cortex.…”
Section: Curiosity As An Aversive Statementioning
confidence: 99%
“…The noradrenergic and dopaminergic systems both have neuroprotective effects that may maintain cognitive function, well-being, and vigor (see Sakaki et al 2018). Therefore, curiosity may mitigate declines in cognitive functioning with age and keep people healthy and happy by exploring and learning something new (Ruan et al 2018).…”
Section: The Nature Of Curiositymentioning
confidence: 99%
“…An uncertain incentive implies that the exact promised financial outcome remains unknown initially, and at the time, it is not immediately clear whether an individual would want to approach or avoid the unknown (Ely, Frankel, and Kamenica 2015;Golman and Loewenstein 2018;Herrnstein and Prelec 1991;Hertwig and Engel 2016;Loewenstein 1994). However, it is a pleasant experience for the individual to resolve uncertainty (Hsee and Ruan 2016;Ruan, Hsee, and Lu 2018; also see neural evidence: Peysakhovich and Karmarkar 2016;and animal research: McDevitt et al 2016). After the individual has had this resolution experience and has gone through repetitions as such, she will eventually realize that an uncertain incentive not only offers a financial benefit with an unknown magnitude (which she knew from the beginning), but also promises a pleasant experience of discovering the unknown with his action.…”
Section: Our Predictionsmentioning
confidence: 99%
“…When an incentive is uncertain, the outcome acquisition utility may be high (if one receives the best outcome in the uncertain incentive) or low (if one receives the worst outcome). However, regardless of the size of the outcome acquisition utility, the uncertainty resolution utility remains positive, because one always moves from an undesirable state of not knowing to a desirable state of knowing (Ruan et al 2018). That is, even if the mobile payment user does not always receive the best outcome ($4), she may still keep tapping her phone to pay for the pleasure of discovering which cash reward she will receive next time.…”
Section: Our Predictionsmentioning
confidence: 99%